Quasi-static and pseudo-dynamic testing of unbonded post-tensioned rocking bridge piers with external replaceable dissipaters. - Marriott, Dion (Earthquake engineering & structural dynamics.)
It has been well documented that following a major earthquake a substantial percentage of economic loss results from downtime of essential lifelines in and out of major urban centres. This has thus led to an improvement of both performance-based seismic design philosophies and to the development of cost-effective seismic structural systems capable of guaranteeing a high level of protection, low structural damage and reduced downtime after a design-level seismic event. An example of such technology is the development of unbonded post-tensioned techniques in combination with rocking?dissipating connections. In this contribution, further advances in the development of high-performance seismic-resistant bridge piers are achieved through the experimental validation of unbonded post-tensioned bridge piers with external, fully replaceable, mild steel hysteretic dissipaters. The experimental response of three 1 : 3 scale unbonded, post-tensioned cantilever bridge piers, subjected to quasi-static and pseudo-dynamic loading protocols, are presented and compared with an equivalently reinforced monolithic benchmark. Minimal physical damage is observed for the post-tensioned systems, which exhibit very stable energy dissipation and re-centring properties. Furthermore, the external dissipaters can be easily replaced if severely damaged under a major (higher than expected) earthquake event. Thus, negligible residual deformations, limited repair costs and downtime can be achieved for critical lifeline components. Satisfactory analytical?experimental comparisons are also presented as a further confirmation of the reliability of the design procedure and of the modelling techniques.